ANALISIS STRATEGI PEMASARAN SYARI’AH TERHADAP TINGKAT PENJUALAN FASHION MUSLIM DI RANGKASBITUNG - Maskur Maskur; budiman budiman (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2022)
The number of various Muslim clothing sales centers resulted in consumers being given many choices of product types. making it difficult to increase the number of customers in the existing market so that it affects the level of sales. An appropriate marketing strategy is needed to win the competition with similar businesses. This research is a research that aims to test whether the Islamic marketing strategy has an effect on the level of sales and how much the influence of the Islamic marketing strategy on the level of sales. This research is a quantitative method with 43 research respondents. The analytical method used is simple linear regression analysis, classical assumption test, with partial regression test (t-test) and coefficient of determination test (R2). Based on the results of the research conducted, there is a significant influence between the Islamic marketing strategy on the level of product sales. With a significance of 0.001 < 0.005 and the value of t: the value of Fcount 8.436 > Ftable 2.01954, it can be concluded that the Islamic marketing strategy variable has a significant effect on product sales. The magnitude of the influence of the Islamic marketing strategy on the level of product sales is 63.4%. It can be seen that the correlation value (R) is 0.797 with an output coefficient of determination of 0.634 or 0 < R2 (0.634) < 1, stating that the Islamic marketing strategy has an influence on sales levels of 63.4%.